What Works for Learning Pragmatics Online? EFL Students’ Views on Flipped, Independent, and Lecture-Based Modalities - Daniel Ginting; Kartika Nuswantara; Marsha Lavania Manivannan; Hema Rosheny Mustafa; Yusawinur Barella (Universitas Hamzanwadi, 2025)
This study examined students’ perceptions of three online modalities for learning pragmatics during a semester marked by expanded remote instruction. Fourteen English majors in one pragmatics course selected a preferred modality and completed the course across sixteen meetings: lecture based online instruction (n = 5), independent study (n = 5), or a flipped classroom (n = 4). Using a descriptive qualitative design, semi structured interviews were conducted after the course and analyzed through thematic analysis. Students in the flipped classroom reported stronger preparation for live sessions, higher confidence to participate, and deeper contextual understanding through discussion, case analysis, and role play. Independent study afforded flexibility, opportunities for reflection, and repeated exposure to instructor videos and texts, but motivation, isolation, and uncertainty without real time dialogue were common. Lecture based online instruction delivered clear structure and concrete examples but limited active engagement. Across modalities, perceived effectiveness hinged on instructional design, including careful management of cognitive load, concise and segmentable pre class materials, and purposeful use of synchronous time for analysis of authentic pragmatic data such as cooperative principles, speech acts, and politeness strategies. The findings suggest that a well-designed flipped model can support online pragmatic learning when students are prepared and materials are accessible, yet no single approach is universally optimal. Limitations include a small, self-selected sample and reliance on self-reported perceptions. Future research should examine long term learning outcomes, the interaction between learner characteristics and design features, and integrated flipped designs that combine strengths of the three modalities.